Targeting ErbB‐1 and ErbB‐4 in irradiated head and neck cancer: Results of in vitro and in vivo studies. Issue 3 (24th February 2012) - Barnea, Itay; Haif, Sasha; Keshet, Rom; Karaush, Vicky; Lev‐Ari, Shahar; Khafif, Avi; Shtabsky, Alexander; Yarden, Yosef; Vexler, Akiva; Yosef, Rami Ben
Abstract Background ErbB oncogenes have a major role in cancer. The role of ErbB‐4 in cancer cell biology and the effect of anti‐ErbB‐1 and anti‐ErbB‐4 monoclonal antibodies were evaluated in this study. Methods ErbB‐4 expression and binding was evaluated by Western blot, enzyme‐linked immunosorbent assay (ELISA), fluorescent microscopy, and flow cytometry. Cell survival was measured by XTT assay. Tumor progression was followed up in nude mice model. Results High ErbB‐1 levels in head and neck cancer cell lines were determined, whereas ErbB‐4 expression varied. Specific antibody binding to the cells was demonstrated. High ErbB‐4 expressing squamous cell carcinoma 1 (SCC‐1) cells proliferated faster and generated faster growing tumors in mice. Cetuximab and mAb‐3 reduced cell survival proportional to ErbB‐1 and ErbB‐4 expression. Combination of antibodies with irradiation was most effective in reducing cell survival and tumor growth. Conclusion ErbB‐4 plays a role in head and neck cancer cell biology. Anti‐ErbB‐4 targeted therapy can serve as a new strategy against head and neck cancer when combined with established treatments. © 2012 Wiley Periodicals, Inc. Head Neck, 2013